Targeting KIF20A: a new frontier in cancer treatment revealed by multi-omics analysis - Zhang, Jie; Li, Guanghao; Qi, Chunling; Yang, Mingshan; Guo, Wei (Frontiers in Immunology, 2026)
BackgroundKinesin family member 20A (KIF20A), a microtubule-dependent motor protein of the Kinesin superfamily, is involved in cell division and organelle transport. Its expression is dysregulated in various cancers and is closely related to tumor metastasis and patient prognosis. However, its specific functions in different tumor types and the potential as an anticancer target have not been fully elucidated, and a systematic pan-cancer analysis is lacking.MethodsThis study integrated multiple cancer database resources and systematically analyzed the multi-omics alterations of KIF20A in different cancers using R software, including gene expression, genomic variation, methylation status, biological pathways, and clinical value. In addition, we evaluated the regulatory role and immunotherapy potential of KIF20A in the tumor microenvironment through various bioinformatics algorithms. Finally, we explored the impact of KIF20A on the biological behaviors of Kidney Renal Clear Cell Carcinoma (KIRC) cells through in vitro and in vivo experiments.ResultsKIF20A is localized in the nucleus and participates in the cell cycle process, serving as a core gene for tumor cell growth. It undergoes copy number alterations in various tumors, and its high expression is closely associated with clinical progression, poor prognosis, and activation of classical oncogenic pathways in multiple cancers. Mechanistically, aberrant epigenetic modifications and mutations in hallmark pathways are significant reasons for the dysregulated expression of KIF20A. Furthermore, the expression of KIF20A correlates with immune cell infiltration and the expression of immune checkpoint molecules, impacting the efficacy of immunotherapy in various cancers. In vitro experiments have confirmed that interfering with KIF20A expression can effectively inhibit the proliferation, migration, and invasion of KIRC cells. Furthermore, in vivo experimental results indicate that interfering with KIF20A can inhibit tumor growth in nude mice.ConclusionTo our knowledge, this is the first study to reveal the role of KIF20A in tumorigenesis and development from a pan-cancer multi-omics perspective, providing solid theoretical and experimental evidence for KIF20A as a potential anti-cancer therapeutic target.